Developing a sustainable, dynamic, and long-term optimization model of an integrated energy supply system while considering renewable energy storage technologies for a residency building through different climates - Sara Azamian (Next Sustainability)
Achieving sustainable energy development critically depends on restructuring the energy system and transitioning to renewable sources. Two factors within Iran that exacerbate the severity of this issue should be noted: substantial potential for renewable energy and the substandard efficiency of its energy systems that necessitate urgent attention and replacement. Reliability and 24-hour availability pose significant challenges for renewable energy resources; therefore, implementing effective energy storage technologies within an integrated energy system is essential. Furthermore, it is essential to consider the characteristics of climatic zones that influence energy demand patterns and the potential for renewable energy. The household sector presents significant opportunities for exploring these concepts. This study aims to determine the optimal long-term structure for an integrated heat and power supply system that uses renewable energy storage technologies in a residential building across five different climatic zones in Iran. The optimization focuses on minimizing total costs by considering the social cost of emissions alongside other system costs. The optimization problem is linear, dynamic, and multi-criteria. The considered technologies include renewables, energy storage, integrated heating and power supply, recycling, and environmentally friendly technologies, assessed to determine if this replacement is feasible or if the current system remains preferable. The results indicate that it is not only optimal to replace the current energy system but also feasible to create a zero-emission system in some zones. This transition will reduce emissions by 429,000 tons, equivalent to 79.3 million USD over 10 years in a warm and arid zone.